How Vulnerable Are Pollen-Specialist Solitary Bees to Temperature-Mediated Shifts in the Timing of Food Availability? - Gauthier, Gabriel (Université d'Ottawa / University of Ottawa, 2019)
Rising temperatures are advancing the seasonal timing of flowering and pollinator activity in numerous systems. However, if the phenologies of mutualistic partners shift at different rates, a change in temporal overlap may arise. We know that experimental bee–plant mismatch can reduce solitary bee fitness, but we remain unaware whether such mismatches occur in nature—or the extent to which bee–plant synchronization impacts bee populations in real-world conditions. I studied populations of Osmia iridis, a specialist solitary bee dependent on flowers of the plant tribe Fabeae, in the Colorado Rocky Mountains. I used a dataset on timing of bee emergence, bee reproductive output, flowering phenology, and site-level temperatures collected at multiple study sites between 2008 and 2019. I found that the timing of flowering of Lathyrus lanszwertii, the most abundant Fabeae species (which normally peaks after most bees have emerged), is more thermally sensitive than the timing of O. iridis emergence. As a result, L. lanszwertii phenology advances to a greater extent than O. iridis phenology at higher temperatures, leading to greater synchronization of bee emergence with flowering. Contrary to expectations, variation in synchrony between the partners does not predict bee per-capita reproductive output. The increased synchrony observed under warmer conditions is associated with higher bee reproductive output at the population level, but this effect is mainly driven by the highest-elevation site. This site experiences little nesting, likely because bees emerge too early relative to the flowers, thereby preventing large-scale colonization. At the other sites, bee populations seem largely insensitive to variation in the level of bee–plant synchrony. However, warming could eventually result in bees emerging after median flowering at certain sites—an outcome that would likely be damaging for bee populations if they fail to adapt. Understanding the extent to which bees can tolerate shifts in synchrony is paramount given that both species have different phenological responses to temperature and that regional mean spring temperatures are rising quickly.
Keywords: climate change; Megachilidae; mismatch; phenology; reproductive output; temporal overlap